Expression and Function of Organic Cation Transporter 2 in Pancreas - Schorn, Sandra; Dicke, Ann-Kristin; Neugebauer, Ute; Schröter, Rita; Friedrich, Maren; Reuter, Stefan; Ciarimboli, Giuliano (Frontiers in Cell and Developmental Biology, 2021)
Organic cation transporters (OCT) play an important role in mediating cellular uptake of several pharmaceuticals, such as the antidiabetic drug metformin and the platinum-derived chemotherapeutics. Since these drugs can also affect the pancreas, here it was investigated whether these transporters are expressed in this organ. An interaction between OCT2 and the glucose transporter 2 (GLUT2), which is expressed with important functional consequences in the kidneys and in the pancreas, has already been demonstrated elsewhere. Therefore, here it was further investigated whether the two proteins have a functional relationship. It was demonstrated that OCT2 is expressed in pancreas, probably in β cells of Langerhans islets, together with GLUT2. However, a co-localization was only evident in a cell-line model of rat pancreatic β cells under incubation with high glucose concentration. High glucose stimulated OCT2 expression and activity. On the other side, studies conducted in human embryonic kidney cells stably expressing OCT2, showed that overexpression of GLUT2 decreased OCT2 activity. Unfortunately, pull-down experiments aimed to confirm a physical OCT2/GLUT2 interaction were not successful. Renal glucose excretion was reduced in mice with genetic deletion of OCT2. Nonetheless, in these mice no regulation of known kidney glucose transporters was measured. Therefore, it may be speculated that OCT2 may influence cellular trafficking of GLUT2, without changing its amount. OCT2 may play a role in drug uptake of the pancreas, and its activity may be regulated by glucose and GLUT2. Vice versa, GLUT2 activity may be regulated through an interaction with OCT2.